Environment, Energy and Climate Change I - Jimenez, Elena (Springer, 2015)
This volume offers a comprehensive overview of advanced research in the field of environmental green chemistry for air, soil and water pollutants, and presents emerging technologies on the chemical treatment of polluted sites and wastes. The 15 chapters, prepared by internationally respected experts, address the following topics: (1) monitoring of indoor and outdoor air pollutants; (2) atmospheric degradation processes and formation mechanisms of secondary pollutants; (3) the environmental assessment and impacts of soils polluted by heavy metals and hydrocarbons; (4) sustainable and emerging technologies for the chemical treatment of organic and animal wastes and wastewaters; (5) photocatalytic CO2 conversion methods for the mitigation of greenhouse effects; and (6) non-conventional methods in green chemistry synthesis. Lastly, the authors outline the future perspectives of each topic.